A volume integral method for solving scattering problems from locally perturbed infinite periodic layers. Issue 1 (2nd January 2017) - Haddar, Houssem; Nguyen, Thi-Phong
Abstract : We investigate the scattering problem for the case of locally perturbed periodic layers in, . Using the Floquet–Bloch transform in the periodicity direction, we reformulate this scattering problem as an equivalent system of coupled volume integral equations. We then apply a spectral method to discretize the obtained system after periodization in the direction orthogonal to the periodicity directions of the medium. The convergence of this method is established and validating numerical results are provided.